The internationalization of Austrian firms in Central and Eastern Europe - Schien Ninan; Jonas F. Puck (Journal for East European Management Studies, 2010)
We test and expand the Uppsala model with a sample of 109 Austrian companies active in the CEE region, representing 1,271 entries. On the one hand, our expansion of the model is based on collective learning of firms from a specific context, an issue largely neglected in IB research. On the other hand, we expand the model by including two further strategic, i.e. dependent, variables. The paper contributes to research by finding three distinct internationalization processes in CEE, two of them new to the Uppsala Model. Furthermore, the paper strongly supports our argumentation with regard to collective learning and thereby draws new conclusions on learning processes that take place within and between firms over time. – – Dieser Beitrag testet und erweitert das Uppsala Modell anhand eines Samples von 1.271 Markteintritten durch 109 österreichische Firmen in der CEE Region. Unsere Erweiterung bezieht sich einerseits auf kollektives Lernen, ein Phänomen welches bisher in der IB Literatur weitgehend vernachlässigt wurde. Andererseits erweitern wir das Modell durch die Einbeziehung von zwei weiteren abhängigen Variablen. Der Artikel leistet einen Beitrag zur Forschung in dem drei unterschiedliche Internationalisierungsprozesse, zwei davon neu für das Uppsala Model, identifiziert werden. Darüber hinaus unterstützen die Ergebnisse unsere Argumentation des kollektiven Lernens. Dies lässt neue Schlüsse in Bezug auf Lernprozesse, welche innerhalb aber auch zwischen Firmen stattfinden, zu.
Keywords: 650; Austrian companies; CEE region; internationalization processes